MENGGAGAS SUATU KAWASAN INDUSTRI - Sutanto, Sutanto (Gema Teknologi, 2012)
Sutanto, in this paper explain that industrial area is the area where the concentration of industrial activities whose existence the ideal should be integrated with other areas such as residential, office, education, economic activity and other agricultural green belt - the other. This industrial area should be equipped with infrastructure and other support facilities so as to serve the upstream to downstream processes. The necessary infrastructure and facilities such as office managers, environmental facilities, the network - a network of roads, electricity, telecommunications, sewage, water, fire and reforestation. For industrial buildings must meet the requirements of building height, building area coefficient referring to the City Master Plan. Keywords: city master plan